Phytoplasmas of subgroup 16SrIII-J associated with Beta vulgaris in Argentina - Fernandez, Franco Daniel; Guzman, Fabiana; Baffoni, Patricia Andrea; Reinoso, Lucio; Kiehr, Mirta; Delhey, Rolf; Favere, Verónica Mariela; Galdeano, Ernestina; Conci, Luis Rogelio (Springer, 2021)
Symptoms of general wilting and yellowing were found affecting Beta vulgaris L. (sugar beet, fodder beet and chard) in the Argentinean region of Bahía Blanca (Buenos Aires province), Valle Medio, and Valle Inferior de Rio Negro (Patagonia region). PCR amplification of the 16S rRNA region showed presence of phytoplasma in approximately 80% of the samples from symptomatic plants. Phylogenetic analyses revealed the presence of phytoplasmas of the 16SrIII-J subgroup. This is the first molecular evidence of phytoplasmas associated with yellow wilt disease in B. vulgaris in Argentina.